A New Microphallid (Digenea) Species from Lontra provocax (Mammalia: Mustelidae) from Freshwater Environments of Northwestern Patagonia (Argentina) - Flores, Verónica Roxana (2012)
A new microphallid species of Maritrema is described from the native southern river otter, Lontra provocax (Thomas). A naturally infected otter was found dead in the Nahuel Huapi National Park, Argentina. Ovigerous adult worms were recovered from the anterior portion of the intestine. Specimens of Maritrema huillini n. sp. have an unarmed genital pore and glabrous cirrus. They can be distinguished from all other species in the genus by having a long intestinal ceca extending up to three-quarters of the testes length to the level of the posterior border of the testes and a metraterm composed of a proximal sphincter, a non-muscular sac, and a distal muscular portion. This microphallid is the first species recovered from a South American eutherian host and the first digenean recorded for L. provocax.